2004
DOI: 10.1111/j.1365-2672.2004.02208.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bovine manure as fertilizer on the bacteriological quality of organic Iceberg lettuce

Abstract: Aim: To investigate the bacteriological quality, and the occurrence of selected pathogenic bacteria from organically grown Iceberg lettuce fertilized with bovine manure in the form of compost, firm manure and slurry in a 2-year field trial. Methods and Results: Samples of soil, fertilizer, fertilized soil, seedlings and lettuce were analysed for aerobic plate counts (APC), thermotolerant coliform bacteria (TCB), Escherichia coli, E. coli O157:H7, Salmonella spp. and Listeria monocytogenes. No difference in bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 40 publications
4
54
0
Order By: Relevance
“…These results concur with those of a field study in which manure naturally contaminated with E. coli O157:H7 was used as a fertilizer on lettuce, and E. coli O157:H7 was not isolated from the lettuce (16). In contrast, other studies that have investigated the risks of using manure as fertilizer on vegetables have found that transmission may occur under experimental conditions both in greenhouses and in the field (11-14, 23, 29).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…These results concur with those of a field study in which manure naturally contaminated with E. coli O157:H7 was used as a fertilizer on lettuce, and E. coli O157:H7 was not isolated from the lettuce (16). In contrast, other studies that have investigated the risks of using manure as fertilizer on vegetables have found that transmission may occur under experimental conditions both in greenhouses and in the field (11-14, 23, 29).…”
Section: Discussionsupporting
confidence: 55%
“…Samples of soil, manure, and fertilized soil were each mixed manually before appropriate subsamples were weighed into stomacher bags for further processing. The samples from lettuce (heads and outer leaves) were cut into pieces and prepared as described by Johannessen et al (16). For the underdeveloped lettuce and roots, all the material was cut into pieces and used for analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some scientific studies greater risk with the consumption of organic food was not identified [8,13] but controversially, several foodborne disease outbreaks are related to organic food [14]. One example is the outbreak of Shiga toxin-producing Escherichia coli O157:H7 linked with organic 2 Journal of Food Quality Sprinkler irrigation is a method similar to natural rainfall; water is delivered through a pressurized pipe network to sprinklers which spray the water into the air * Source: Solomon et al [23].…”
Section: Introductionmentioning
confidence: 99%
“…While produce contamination with enteric food-borne pathogens is of high public health and economic concern, the contam-ination events are relatively rare (6,12,13), thus requiring intensive but also expensive sampling and testing efforts. A common practice has been to use generic Escherichia coli as an indicator of fecal contamination of produce (5,6,(13)(14)(15).…”
mentioning
confidence: 99%